Oxidative Stress as a Therapeutic Target of Cardiac Remodeling - Martins, Danilo [UNESP]; Garcia, Leonardo Rufino [UNESP]; Queiroz, Diego Aparecido Rios [UNESP]; Lazzarin, Taline [UNESP]; Tonon, Carolina Rodrigues [UNESP]; Balin, Paola da Silva [UNESP]; Polegato, Bertha Furlan [UNESP]; de Paiva, Sergio Alberto Rupp [UNESP]; Azevedo, Paula Schmidt [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Zornoff, Leonardo [UNESP] (MDPI, 2022)
Cardiac remodeling is defined as a group of molecular, cellular, and interstitial changes that clinically manifest as changes in the heart’s size, mass, geometry, and function after different stimuli. It is important to emphasize that remodeling plays a pathophysiological role in the onset and progression of ventricular dysfunction and subsequent heart failure. Therefore, strategies to mitigate this process are critical. Different factors, including neurohormonal activation, can regulate the remodeling process and increase cell death, alterations in contractile and regulatory proteins, alterations in energy metabolism, changes in genomics, inflammation, changes in calcium transit, metalloproteases activation, fibrosis, alterations in matricellular proteins, and changes in left ventricular geometry, among other mechanisms. More recently, the role of reactive oxygen species and oxidative stress as modulators of remodeling has been gaining attention. Therefore, this review assesses the role of oxidative stress as a therapeutic target of cardiac remodeling.
Keywords: antioxidants; cardiac remodeling; heart failure